Static and dynamic evaluation of respiratory muscle strength in asthmatic children and adolescents - Cordeiro,Jean Aretakis (2020)
Abstract Objectives: to evaluate static and dynamic respiratory muscle strength in children and adolescents with asthma. Methods: cross-sectional study, involving 80 children and adolescents, 40 with asthma and 40 healthy controls. Biological and clinical characteristics were analyzed. The analysis of the dynamic inspiratory muscle strength was obtained using the KH5 device of the POWERbreathe® line, while the static evaluation was performed using an analog manova-cuometer. Results: the mean obtained from the S-Index was higher in the control group compared to asthmatics (p = 0.026). There was no statistical difference between MIP values for asthmatics and predicted values (p = 0.056). The MEP results showed a significant difference between the mean of the cases and the predicted values (p = 0.000). There was a positive correlation between height and S-Index (p = 0.002 and r = 0.438). Conclusion: the present study demonstrated that the static inspiratory muscle strength (PImáx) of children and adolescents with asthma in comparison with the values predicted in the literature does not differ, however, when submitted to dynamic assessment (S-Index), it presents higher values in healthy controls. In addition, the S-Index showed a positive correlation with the child's height.